Metabolic Adaptation of Human CD4+ and CD8+ T-Cells to T-Cell Receptor-Mediated Stimulation - Jones, Nicholas; Cronin, James G.; Dolton, Garry; Panetti, Silvia; Schauenburg, Andrea J.; Galloway, Sarah A. E.; Sewell, Andrew K.; Cole, David K.; Thornton, Catherine A.; Francis, Nigel J. (Frontiers in Immunology, 2017)
Linking immunometabolic adaptation to T-cell function provides insight for the development of new therapeutic approaches in multiple disease settings. T-cell activation and downstream effector functions of CD4+ and CD8+ T-cells are controlled by the strength of interaction between the T-cell receptor (TCR) and peptides presented by human leukocyte antigens (pHLA). The role of TCR-pHLA interactions in modulating T-cell metabolism is unknown. Here for the first time we explore the relative contributions of the main metabolic pathways to functional responses in human CD4+ and CD8+ T-cells. Increased expression of hexokinase II accompanied by higher basal glycolysis is demonstrated in CD4+ T-cells; cytokine production in CD8+ T-cells is more reliant on oxidative phosphorylation. Using antigen-specific CD4+ and CD8+ T cell clones and altered peptide ligands we demonstrate that binding affinity tunes the underlying metabolic shift. Overall this study provides important new insight into how metabolic pathways are controlled during antigen-specific activation of human T-cells.